Drug overdose deaths among women 1999–2021 in the United States: Differences by race, ethnicity, and age - Abenaa A Jones; Joel E Segel; Emma M Skogseth; Hannah B Apsley; Alexis R Santos-Lozada (Women's Health)
Background: The U.S. drug overdose epidemic is increasingly severe and steep increases have been seen among women. Objective: To explore trends in drug overdose deaths among women in the United States by race, ethnicity, and age group. Design: This study is a retrospective observational study of drug overdose deaths among U.S. women from 1999 to 2021. Methods: We use CDC WONDER Multiple Causes of Death files data using International Classification of Diseases, 10th Revision (ICD-10) codes X40–X44, X60–X64, X85, and Y10–Y14 to identify overall drug overdose deaths, T40.5 for cocaine-related deaths, T40.0–T40.4, T40.6 for opioid-related deaths, T42.4 for benzodiazepines, and T43.6 to identify psychostimulants. Race and ethnicity were defined as non-Hispanic Black, White, American Indian/Alaska Native (AI/AN), Asian, and Hispanic. We calculated overdose death rates per 100,000 women for all overdose deaths and for specific drugs by year, stratified by race and ethnicity. Results: From 1999 to 2021, overdose deaths among all women in the United States increased by 480%. Overdose deaths rose 750% for non-Hispanic AI/AN women, 490% for non-Hispanic Black women, 450% for non-Hispanic White women, 325% for Hispanic women, and 150% for non-Hispanic Asian or Pacific Islander women. Women ages 35–44 and 45–54 saw the largest increases in overall overdose deaths. Cocaine-related deaths were more prevalent among non-Hispanic Black women, opioid and methamphetamine-related deaths were more prevalent among non-Hispanic AI/AN women, and benzodiazepine-related deaths were more prevalent among non-Hispanic White women. Conclusion: Increases in overdose deaths were noted in all races, ethnicities, and age groups, with deaths continuing to accelerate in 2021. Our study highlights a need for interventions expanding access to medications for opioid use disorder, naloxone, fentanyl test strips, and contingency management while accounting for gendered roles and vulnerabilities.